Difficulties in Translating Conjunctions in Arabic and English Languages: Study Based On Translation Students of South Eastern University Of Sri Lanka - NM Mohamed Rizvi; MHA Munas; Iqbal Saujan (Indonesian Journal of Arabic Studies, 2021)
Each language has its own set of rules. Based on this, the rule of conjunctions in the Arabic language differs from the English language, because they come from two separate language families. Thus, the learners of Arabic and English languages as a foreign language face difficulty and commit mistakes in identifying meanings of conjunctions. Therefore, this Study focuses on identifying difficulties when translating. This study employed a descriptive and contrastive methodology. The data were gathered from interviews and questionnaire that were distributed to all specialization Students in linguistic and translation from South Eastern University of Sri Lanka. MS Excel Software was used for the data analysis. The findings show, the students face difficulties in determining appropriate conjunctions and understanding their meaning, using suitable words. Based on the researcher's findings, continuous training in translation with caring of grammatical errors is recommended. This research will help foreign language learners, translators and studentsÙƒÙ„ Ù„ØºØ© Ù„Ù‡Ø§ Ù…Ø¬Ù…ÙˆØ¹Ø© Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ø®Ø§ØµØ© Ø¨Ù‡Ø§. ÙˆØ¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ Ø°Ù„Ùƒ ØŒ ÙØ¥Ù† Ù‚Ø§Ø¹Ø¯Ø© Ø§Ù„Ø§Ù‚ØªØ±Ø§Ù† ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ØªØ®ØªÙ„Ù Ø¹Ù† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© ØŒ Ù„Ø£Ù†Ù‡Ø§ ØªØ£ØªÙŠ Ù…Ù† Ø¹Ø§Ø¦Ù„ØªÙŠÙ† Ù„ØºÙˆÙŠØªÙŠÙ† Ù…Ù†ÙØµÙ„ØªÙŠÙ†. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ØŒ ÙŠÙˆØ§Ø¬Ù‡ Ù…ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù„ØºØªÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø¥Ù†Ø¬Ù„ÙŠØ²ÙŠØ© ÙƒÙ„ØºØ© Ø£Ø¬Ù†Ø¨ÙŠØ© ØµØ¹ÙˆØ¨Ø© ÙˆÙŠØ±ØªÙƒØ¨ÙˆÙ† Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ ØªØØ¯ÙŠØ¯ Ù…Ø¹Ø§Ù†ÙŠ Ø§Ù„Ø§Ù‚ØªØ±Ø§Ù†. Ù„Ø°Ù„Ùƒ ØŒ ØªØ±ÙƒØ² Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ ØªØØ¯ÙŠØ¯ Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª Ø¹Ù†Ø¯ Ø§Ù„ØªØ±Ø¬Ù…Ø©. Ø§Ø³ØªØ®Ø¯Ù…Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ù†Ù‡Ø¬Ù‹Ø§ ÙˆØµÙÙŠÙ‹Ø§ ÙˆÙ…Ù‚Ø§Ø¨Ù„Ù‹Ø§. ØªÙ… Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø§Øª ÙˆØ§Ù„Ø§Ø³ØªØ¨ÙŠØ§Ù†Ø§Øª Ø§Ù„ØªÙŠ ØªÙ… ØªÙˆØ²ÙŠØ¹Ù‡Ø§ Ø¹Ù„Ù‰ Ø¬Ù…ÙŠØ¹ Ø·Ù„Ø§Ø¨ Ø§Ù„ØªØ®ØµØµ ÙÙŠ Ø§Ù„Ù„ØºÙˆÙŠØ§Øª ÙˆØ§Ù„ØªØ±Ø¬Ù…Ø© Ù…Ù† Ø¬Ø§Ù…Ø¹Ø© Ø¬Ù†ÙˆØ¨ Ø´Ø±Ù‚ Ø³Ø±ÙŠÙ„Ø§Ù†ÙƒØ§. ØªÙ… Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¨Ø±Ù†Ø§Ù…Ø¬ MS Excel Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª. ØªØ¸Ù‡Ø± Ø§Ù„Ù†ØªØ§Ø¦Ø¬ Ø£Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ ÙŠÙˆØ§Ø¬Ù‡ÙˆÙ† ØµØ¹ÙˆØ¨Ø§Øª ÙÙŠ ØªØØ¯ÙŠØ¯ Ø§Ù„Ø§Ù‚ØªØ±Ø§Ù†Ø§Øª Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø© ÙˆÙÙ‡Ù… Ù…Ø¹Ø§Ù†ÙŠÙ‡Ø§ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø©. Ø¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨Ø§ØØ« ØŒ ÙŠÙˆØµÙ‰ Ø¨Ø§Ù„ØªØ¯Ø±ÙŠØ¨ Ø§Ù„Ù…Ø³ØªÙ…Ø± ÙÙŠ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ù…Ø¹ Ù…Ø±Ø§Ø¹Ø§Ø© Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ©. Ø³ÙŠØ³Ø§Ø¹Ø¯ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© ÙˆØ§Ù„Ù…ØªØ±Ø¬Ù…ÙŠÙ† ÙˆØ§Ù„Ø·Ù„Ø§Ø¨.